What if expatriates decide to leave? The mediation effect of the psychological contract fulfilment. (19th August 2014) - Cesário, Francisco Santos; Chambel, Maria José; Guillén, Carlos
Abstract : Purpose: The aim of this study is to investigate the relationships among expatriates' perceived human resource management practices, psychological contract fulfillment, and turnover intention. Design/methodology/approach: The study sampled 100 expatriates from a Portuguese company through a survey questionnaire. The paper used SEM analyses to explore relationships between the variables and to test its hypotheses. Findings: The data showed that expatriates' perceived fulfillment of their psychological contracts was negatively related to turnover intention. The study also finds a positive relationship between human resource management practices and the fulfillment of psychological contract. Moreover, expatriates' perceived fulfillment of psychological contract was found to be a mediator between human resource management practices and turnover intention. Thus, a subjective perception of psychological contract fulfillment is an important predictor of turnover intention, but this perception is related with the human resource management practices developed by the organization during the mission. Research limitations/implications: First, the study is limited due to sample nature and the lack of longitudinal design not allowing causal relationships to be established between the variables. Second, all variables were measured using self-reported data, raising the question of whether the results may have been contaminated by common method variance. Practical implications: An important implication from this research is that organizations should develop appropriate HR practices during the mission, and maintain open communications with their expatriates to ensure clear understanding of the agreement existing about the international mission. Originality/value: Few research is available, to the authors' knowledge, to assess HRM practices with a specific measure to expatriation context and with a portuguese expatriation sample